Управління інноваціями на підприємствах харчової промисловості України - Левченко, Юлія Григорівна (My University, 2007)
Проведено аналіз економічної сутності інновацій, внаслідок чого набув подальшого розвитку понятійний апарат організації та управління інноваціями, зокрема такі його елементи як “інновація”, “інноваційна діяльність”, “управління інноваціями”. Запропоновано комплексну оцінку системи управління інноваціями. Проаналізовано сучасний стан і тенденції розвитку інноваційної діяльності підприємств харчової промисловості, у тому числі фінансування інноваційної діяльності підприємств окремих галузей харчової промисловості та ефективність управління інноваціями на підприємствах. Запропоновано модель управління інноваціями, напрями розвитку управління інноваціями та пріоритетні напрями інноваційного розвитку окремих галузей харчової промисловості.

The modern state and tendencies of innovative activity of enterprises of food retail industry, including financing of innovative activity of enterprises of separate industries of food retail industry, is analysed that efficiency of management innovations on enterprises. The scientific novelty of the got results is determined that an author is develop scientific approaches to forming of mechanism of management innovations on the enterprises of food retail industry in the conditions of the modern stage of market transformation economies, certain priority directions of innovative development of food retail industry on the whole and in the cut of separate industries; the measures of improvement of management innovations are offered on the enterprises of food retail industry. In work is offered model management innovations, priority directions of innovative development of separate industries of food retail industry and directions of improvement of management innovations.
Keywords: інноваційна діяльність підприємства; innovative activity; інноваційний потенціал підприємства; управління інноваціями; планування; innovative potential of the enterprise; innovative potential; enterprise; food retail industry; кафедра економіки і права